Developing “Once upon a Box” as a Medium for Reading Activity (RETAIN, 2018)
AbstractIn junior high level, students are required to master, at least three texts, which are descriptive text, personal recount text, and narrative text (Kementerian Pendidikan dan Kebudayaan, 2016).Therefore, it is hard to attract students’ interest on EFL reading activity as they are rarely exposed to the target language in their daily life, so they do not see the importance of EFL reading activity (Mason, 1992). Thus, variations and suitable approach in reading activity are needed. As a result, a learning medium, namely ‘Once upon a Box’, is developed in order to involve students in enjoyable reading activity, enrich students’ vocabulary knowledge, and stimulate students to understand the main idea of the story they read. To develop the product, this study adapted ADDIE approach by Branch (2004). Based on the trials and evaluations, most of the students were giving positive feedback toward the medium. The students are also motivated to read as the illustrations are attractive. In content validation, the medium can be categorized as ‘good’. Meanwhile, in medium validation, the medium can be categorized as ‘excellent’. Fortunately, when the medium is implemented, the use of dictionary can be minimized and the preliminary goals can be met. In short, this paper is aimed to describe the development process of learning medium namely ‘Once upon a box’ for reading activity. Keywords: reading, once upon a box, narrative text, ADDIE AbstrakDi tingkat pendidikan menengah, para siswa paling tidak diharuskan menguasai tiga teks, yaitu teks deskriptif, teks personal recount, dan teks naratif (Kementerian Pendidikan dan Kebudayaan, 2016). Namun, menarik minat para siswa untuk membaca teks berbahasa Inggris tidaklah mudah karena mereka tidak menyadari pentingnya aktivititas tersebut (Mason, 1992). Karena itu, variasi dan pendekatan yang sesuai untuk aktivitas membaca diperlukan. ‘Once upon a Box’ adalah media pembelajaran yang dikembangkan untuk melibatkan siswa dalam kegiatan membaca teks berbahasa Inggris yang menyenangkan, memperkaya perbendaharaan kata siswa, dan mendorong siswa untuk memahami ide pokok dari cerita yang mereka baca. Penelitian ini mengadaptasi pendekatan ADDIE oleh Branch (2004) untuk mengembangkan produk. Dengan kata lain, artikel ini ditujukan untuk mendeskripsikan proses pengembangan media pembelajaran ‘Once upon a Box’ untuk aktivitas membaca.Kata Kunci: membaca, once upon a box, teks naratif, ADDIE